ASSESSING DESCRIPTIVE PARAGRAPH WRITING ABILITY OF THE EIGHTH GRADE STUDENTS OF SMPN 2 SUKAWATI THROUGH GUIDED QUESTION AND ANSWERING ACADEMIC YEAR 2018/2019 - Cahyadi, I Wayan Karang; Krismayani, Ni Wayan; Maharani, Anak Agung Putri (Yavana Bhasha : Journal of English Language Education, 2019)
The researchers was interested in undertaking the study which dealt with assessing descriptive paragraph writing ability of the eighth grade students of SMPN 2 Sukawati through guided question and answer in academic year 2018/2019. It was aimed at figuring out the achievement of the eighth grade students’ descriptive paragraph writing ability at SMPN 2 Sukawati in academic year 2018/2019 which was assessed through guided question and answer. The study was designed in the form of ex-post facto research. There were 50 eighth grade students of SMPN 2 Sukawati in academic year 2018/2019 who were chosen by using random sampling technique with lottery system as the research samples. The data were collected by administering guided question and answer test as the research instrument. The obtained data had been analyzed by using norm reference measure of five standard values. The results of the data analysis showed that (1) 1 or 2% of 50 samples got excellent achievement of descriptive paragraph writing ability, (2) 18 or 36% of 50 samples got good achievement, (3) 15 or 30% of samples got sufficient achievement, (4) 9 or 18% of samples got insufficient achievement, (5) 7 or 14% got poor achievement. It could be concluded that there were 68% of the samples were successful and there were 32% of the samples were unsuccessful in writing descriptive paragraph which was assessed by guided question and answer.